Salinity reduction benefits European eel larvae: Insights at the morphological and molecular level. - Sebastian N Politis; David Mazurais; Arianna Servili; Jose-Luis Zambonino-Infante; Joanna J Miest; Jonna Tomkiewicz; Ian A E Butts (PLoS ONE, 2018)
European eel (Anguilla anguilla) is a euryhaline species, that has adapted to cope with both, hyper- and hypo-osmotic environments. This study investigates the effect of salinity, from a morphological and molecular point of view on European eel larvae reared from 0 to 12 days post hatch (dph). Offspring reared in 36 practical salinity units (psu; control), were compared with larvae reared in six scenarios, where salinity was decreased on 0 or 3 dph and in rates of 1, 2 or 4 psu/day, towards iso-osmotic conditions. Results showed that several genes relating to osmoregulation (nkcc2α, nkcc2β, aqp1dup, aqpe), stress response (hsp70, hsp90), and thyroid metabolism (thrαA, thrαB, thrβB, dio1, dio2, dio3) were differentially expressed throughout larval development, while nkcc1α, nkcc2β, aqp3, aqp1dup, aqpe, hsp90, thrαA and dio3 showed lower expression in response to the salinity reduction. Moreover, larvae were able to keep energy metabolism related gene expression (atp6, cox1) at stable levels, irrespective of the salinity reduction. As such, when reducing salinity, an energy surplus associated to reduced osmoregulation demands and stress (lower nkcc, aqp and hsp expression), likely facilitated the observed increased survival, improved biometry and enhanced growth efficiency. Additionally, the salinity reduction decreased the amount of severe deformities such as spinal curvature and emaciation but also induced an edematous state of the larval heart, resulting in the most balanced mortality/deformity ratio when salinity was decreased on 3 dph and at 2 psu/day. However, the persistency of the pericardial edema and if or how it represents an obstacle in further larval development needs to be further clarified. In conclusion, this study clearly showed that salinity reduction regimes towards iso-osmotic conditions facilitated the European eel pre-leptocephalus development and revealed the existence of highly sensitive and regulated osmoregulation processes at such early life stage of this species.